Diagénesis del Cretácico superior manchego. - Fernández Calvo, C. (Cuadernos de Geología Ibérica, 1982)
The study of the diagenetic processes from Upper Cretaceous of La Mancha is very useful to understand some sedimentological caracteristics and the evolution of the basin. The dolomitization, whose analysis at several seales has permited us to distinguish two types of dolomites with a different origin, is discussed in detail here. 1.